1972
DOI: 10.1139/v72-417
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and Electronic Spectral Studies of Cobalt(II) and Nickel(II) Complexes of N-Allyl Urea and N-Allyl Thiourea

Abstract: Complexes of N-ally1 urea (NAU) and N-ally1 thiourea (NATU) with cobalt(I1) and nickel(I1) halides and perchlorates have been prepared and characterized by electrical conductance, magnetic susceptibility, infrared and electronic spectra. Infrared spectra suggest coordination in NAU through oxygen and in NATU through nitrogen. The electronic spectra and magnetic susceptibility data indicate tetrahedral and octahedral stereochemistry for cobalt(I1) and nickel(I1) halide complexes, respectively. The various ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Indeed, the bands at 351 and 333 nm ascribe π–π* ligand transitions in the complexes and this at 504 nm in the spectrum of C1 is due to charge transfer from a filled d‐orbital of cobalt to a ligand antibonding π* orbital 67 . In fact, the tetrahedral Co (II) complexes should exhibit three d–d absorption bands due to 4 A2normalg()F– 4 T2normalg()F, 4 A2normalg()F– 4 T1normalg()F, and 4 A2normalg()F– 4 T1normalg()P transitions; however, the former two peaks were not detected due to expected occurrence at very high wavelengths (>1250 nm) and the peaks at 563 and 659 nm for the complexes are due to the latter transition 68,69 . This determined geometry for the complexes is supported by magnetic moment values (4.49–4.52 BM) close to reported values for other tetrahedral cobalt compounds with three unpaired electrons 67…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the bands at 351 and 333 nm ascribe π–π* ligand transitions in the complexes and this at 504 nm in the spectrum of C1 is due to charge transfer from a filled d‐orbital of cobalt to a ligand antibonding π* orbital 67 . In fact, the tetrahedral Co (II) complexes should exhibit three d–d absorption bands due to 4 A2normalg()F– 4 T2normalg()F, 4 A2normalg()F– 4 T1normalg()F, and 4 A2normalg()F– 4 T1normalg()P transitions; however, the former two peaks were not detected due to expected occurrence at very high wavelengths (>1250 nm) and the peaks at 563 and 659 nm for the complexes are due to the latter transition 68,69 . This determined geometry for the complexes is supported by magnetic moment values (4.49–4.52 BM) close to reported values for other tetrahedral cobalt compounds with three unpaired electrons 67…”
Section: Resultsmentioning
confidence: 99%
“…67 In fact, the tetrahedral Co (II) complexes should exhibit three d-d absorption bands due to 4 and 4 A 2g F ð Þ-4 T 1g P ð Þ transitions; however, the former two peaks were not detected due to expected occurrence at very high wavelengths (>1250 nm) and the peaks at 563 and 659 nm for the complexes are due to the latter transition. 68,69 This F I G U R E 1 Crystal structure of complex C1 with thermal ellipsoids at 50% probability level.…”
Section: Synthesis and Spectroscopic Characterizationmentioning
confidence: 99%
“…Nickel(II) halide complexes of N-allyl urea (NAU) and N-allyl thiourea (NATU) have been studied and their structures have been established with the help of infrared and electronic spectral studies and other physicochemical measurement. These studies have confirmed that both have octahedral structure and the ligand is coordinated to nickel through its oxygen in NAU 1,2 and through its sulphur in NATU [3][4][5] . We have made molecular orbital calculations of the complexes and have evaluated eigenvalue, eigenvector and overlap matrix parameters.…”
Section: Introductionmentioning
confidence: 82%